Contributions of depression and body mass index to body image. (August 2018) - Paans, Nadine P.G.; Bot, Mariska; Brouwer, Ingeborg A.; Visser, Marjolein; Penninx, Brenda W.J.H.
Abstract: Depression and body mass index (BMI) are known to be associated with body image, however, their independent or joint effects on body image in adults are largely unknown. Therefore, we studied associations of depression diagnosis, severity, and BMI with perceptual body size (PBS) and body image dissatisfaction (BID). Cross-sectional data from 882 remitted depressed patients, 242 currently depressed patients and 325 healthy controls from the Netherlands Study of Depression and Anxiety were used. Depressive disorders (DSM-IV based psychiatric interview), standardized self-reported depressive symptoms (Inventory of Depressive Symptomatology) and BMI were separately and simultaneously related to body image (the Stunkard Figure Rating scale) using linear regression analyses. Thereafter, interaction between depression and BMI was investigated. Analyses were adjusted for demographic and health variables. Higher BMI was associated with larger PBS (B = 1.13, p < .001) and with more BID (B = 0.61, p < .001). Independent of this, depression severity contributed to larger PBS (B = 0.07, p < .001), and both current (B = 0.21, p = .001) and remitted depression diagnosis (B = 0.12, p = .01) as well as depression severity (B = 0.11, p < .001) contributed to BID. There was no interaction effect between BMI and depression in predicting PBS and BID. In general, depression (current, remitted and severity) and higher BMI contribute independently to a larger body size perception as well as higher body image dissatisfaction. Efforts in treatment should be made to reduce body dissatisfaction in those suffering from depression and/or a high BMI, as BID can have long-lasting health consequences, such as development of anorexia and bulimia nervosa and an unhealthy lifestyle. Highlights: Major depressive disorder is related to higher body image dissatisfaction. High depressive symptoms are associated to higher body image dissatisfaction. High depressive symptoms are associated to a larger perceptual body size. High BMI is associated to a larger perceptual body image and more dissatisfaction. Associations between depression and body image do not vary across BMI levels.